Os gêneros Eriosema e Rhynchosia (Leguminosae - Papilionoideae - Phaseoleae) no nordeste brasileiro - Oliveira, Ana Carla Da Silva (2018)
Abstract Eriosema and Rhynchosia are the only genera of subtribe Cajaninae which include species that occur in tropical and subtropical regions in both hemispheres. Previous taxonomic studies related to both genera were carried out only in specific areas of different regions of the country, including descriptions of new species. Regarding the Northeast region, these studies are still incipient. This work aimed to perform the taxonomic study of the species of both genera that occur in the Northeast region of the country. To accomplish this, voucher specimens deposited at 18 herbaria and individuals collected by our team were analyzed. In total, 14 taxa were recorded, seven belonging to Eriosema (E. campestre, E. congestum, E. crinitum, E. floribundum, E. rufum, E. simplicifolium, and E. venulosum), and seven belonging to Rhynchosia (R. claussenii, R. edulis, R. melanocarpa, R. minima, R. naineckensis, R. phaseoloides, and R. reticulate). The species R. claussenii and E. floribundum are cited for the first time in Northeast. New records were also found in some states such as E. campestre (Maranhão), E. floribundum (Bahia), E. rufum (Ceará, Piauí), R. edulis (Alagoas), and R. reticulata (Pernambuco). To help the identification of the species, identification keys, descriptions, and illustrations of all taxa are provided.